A smaller bearing ratio, as a surface texture measure, promotes faster sliding on ice - Jansons, E.; Lungevics, J.; Jerane, I.; Gross, K. A. (Journal of Tribology, 2021)
Surfaces only characterized by a roughness Ra or Sa may have a totally different surface texture and include complex patterns such as grooves, dimples, or a mirror-polish. Here, the bearing ratio is proposed as an additional characterization measure to determine the sliding performance of a steel-ice friction pair. Different steel surfaces were produced by milling, shot blasting, and scratching, followed by texture assessment with a stylus type three-dimensional (3D) profilometer. The bearing ratio and other 3D roughness parameters were determined. Tribology experiments involved a 3 m long inclined plane tribometer and the speed measured at four points during the sliding experiment. Correlation between the steel sliding speed and the bearing ratio was observed under two different regimes: at warmer conditions and at colder conditions. Experiment 1 depicting warmer conditions exhibited a relative humidity of 64%, an air temperature of -2 °C, and an ice temperature of -9 °C. Experiment 2 for colder conditions showed a relative humidity of 78%, an air temperature of 1 °C, and an ice temperature of -4 °C. The sliding speed correlated with the bearing ratio in these two conditions showing -0.91 and -0.96, respectively. A strong correlation between the sliding speed and the bearing ratio shows the value of the bearing ratio as an additional surface characteristic for considering larger surface features.